The upper bound of thin-film composite (TFC) polyamide membranes for desalination - Yang, Zhe; Guo, Hao; Tang, Chuyang Y. (Journal of membrane science, 2019)
Membrane separation properties are constrained by a tradeoff relationship between permeability and selectivity. This tradeoff relationship has been well established for gas separation membranes in the form of the Robeson's upper bound. In contrast, the upper bound relationship is much less established for thin-film composite (TFC) polyamide membranes used for desalination. In this work, we analyzed the tradeoff between the water permeance and the water/NaCl selectivity for TFC membranes gathered from more than 300 published papers. A clear upper bound behavior relationship is established, and the various effects of membrane synthesis conditions and modifications are reviewed in relation to this permeance-selectivity tradeoff. Our work provides a critical tool for the evaluation and benchmarking of future membrane development works in the context of desalination and water reuse. [Display omitted] •TFC polyamide membranes are constrained by permeance-selectivity tradeoff.•An upper bound is established based on TFC membranes from >300 papers.•The upper bound is given by A/B = 16000A−3.2 (A/B in bar−1 and A in Lm−2h−1bar−1).•The effects of various parameters on membrane performance are summarized.